Addressing Teachers on the issues of new textbooks in English Language: An experience through video conference - Patel, Madhulika S.; Khar, Meenakshi (JOURNAL OF INDIAN EDUCATION, 2010)
This paper presents a brief report of a interactive session during videoconferencing programme organised for assessing and addressing teachers’ understanding about new textbooks of English Language developed by NCERT for Classes I to XII on the basis of National Curriculum Framework-2005. The inputs received from a group of about 6070 English teachers through their direct interaction with experts on NCF-2005,new syllabi and textbooks is valuable towards undertaking exercise on continual improvement of textbooks and development of related educational materials for qualitative improvement of education in the country. All the reflections, views, observations, suggestions and also questions/queries on different aspects of curriculum framework, syllabi, textbooks made by the language teachers teaching English from Classes I to XII are analysed by the subject experts and interpretations were made. These are available with the NCERT for the use of teachers who are teaching English from Classes I to XII and have not attended the video conferencing on the use of new textbooks developed by NCERT.